Sosialisasi Kesetaraan Gender: Keterlibatan Perempuan dalam Kegiatan Pertanian Keluarga di Desa Sri Tanjung - Lubis, Syahrika Ardiyani; Wijayanti, Ayu; Heriyanti, Lesti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Gender equality means justice between women and men in the opportunity to achieve a better life. In the world of agriculture, women's involvement is already quite large, but there is still a problem of gender inequality. In rural areas, agriculture is the main economic activity of the community. Sri Tanjung Village, Central Semende Darat Subdistrict, Muara Enim Regency, has highlands and fertile land so that the people of Sri Tanjung Village generally work as farmers. Therefore, this socialization activity was held to find out the involvement of women's roles as family farmers, especially in the Sri Tanjung Village environment. This socialization activity includes educating the community about gender and gender inequality in agricultural activities, in order to create justice in family farming activities. In the activity there was a presentation of material by MSIB students and a discussion session that discussed about The implementation methods of socialization activities are: preparation, implementation, presentation, and evaluation. This socialization activity was supported by village officials, Village Forest Management Institution (LPHD) officials, Forest Farmers Group (KTH), and Sri Tanjung Village community. After this socialization activity, it is hoped that the community will gain insight related to the meaning of gender equality, especially in farming activities and give women the opportunity to make decisions.